Corrigendum/ Erratum/ Retraction - Jurnal Istawa (ISTAWA, 2019)
Retraction to:Subhan, M. (2019). Penerapan Corporate Governance Perguruan Tinggi Islam. Istawa: Jurnal Pendidikan Islam, 3(2), 155-176. doi:http://dx.doi.org/10.24269/ijpi.v3i2.1504This article has been retracted by the publisher based on the following reasonThis is based on the original author's report and the author's acknowledgement that plagiarized to the editor that the author committed an ethical violation of the publication. The author acknowledges that he has plagiarized other writers' scripts. Plagiarism articles have been published in Lentera Journal (Publisher: STAIM Nglawak, Nganjuk, East Java, Indonesia) Vol 18 No 1 (2019): March 2019 (https://ejournal.staimnglawak.ac.id/index.php/lentera/article/view/116)This article has followed the procedures that apply to journal management. The author has received the review results and has improved the article according to the review result.One of the conditions of submission of a paper for publication in this journal is that authors declare explicitly that their work is original and has not appeared in a publication elsewhere, and also not considered by another journal. As such this article represents a severe abuse of the scientific publishing system. The scientific community takes a very strong view on this matter, and apologies are offered to readers of the journal that this was not detected during the submission process.